检验减速器疲劳强度方法和装置的研究 - 贾铁钢 (Jixie chuandong)
The continuous operation fatigue strength of washing machine reducer（trouble-free operation） test is the first article inspection into the plant must be checked items.In order to quickly check washing machine reducer fatigue strength,using failing moment（static failure strength） instead of the fatigue strength test is presented through comparative test.The reason of using this test method is given,the structure of inspection of washing machine reducer failing moment test device is determined.